Alternative Litigation Financing in the United States Issues, Knowns, and Unknowns - Garber, Steven (RAND Corporation, 2010)
Alternative litigation financing (ALF)--also known as "third-party" litigation financing--refers to provision of capital by parties other than plaintiffs, defendants, their lawyers, or defendants' insurers to support litigation-related activity. This paper describes the ALF industry as of early 2010 and discusses the legal ethics, social morality, and, especially, potential economic effects of ALF.